Method for forming the portfolio of projects to reduce losses in electric networks based on the lean approach and a feeder-to-feeder analysis - Achkasov, Igor; Boiko, Yevheniia; Pushkar, Tetiana; Vykhodets, Yuliya (Eastern-European Journal of Enterprise Technologies, 2018)
This research aims to develop an approach for forming the portfolio of projects for reducing losses in distributive electric networks. The purpose of this paper is to substantiate the selection of projects for reducing losses in distributive networks for the portfolio of projects. The project management of the reduction of losses is based on the principles of value-oriented organization and economic production. We proposed a step-by-step method of formation of a portfolio of projects for reducing losses, in which it was proposed to use a feeder as the unit of analysis. This approach enables a power supply company to create the optimal portfolio of projects by the criteria of value, risks and costs. The portfolio of the projects for reducing electric power losses in distributive networks of a power supply company includes a set of technical and organizational projects. The proposed approach to formation of the projects’ portfolio includes five stages. Stage 1 involves the identification of the components of the portfolio projects, the basic among which are initiatives, projects, programs, and sub-projects. The projects are grouped at stage 2. To group the projects, we proposed four templates that characterize technical and organizational projects in the portfolio. Stage 3 involves evaluation and selection of projects by the quantitative and qualitative indicators. Value, risks and costs were determined as the main criteria to substantiate the selection of projects. The analytical sample of the projects according to given criteria becomes the basis for the selection of projects. Stage 4 implies prioritization of projects by their ranking. Ranking is performed by means of comparing the values of the indicators of value and attractiveness of a project by the project group or by the entire portfolio of projects. Stage 5 implies balancing the projects’ portfolio by identifying discrepancies between the indicators of project groups and «smoothing». Based on the formed portfolio, the flexibility of losses reduction management increases, since it makes it possible to redistribute the composition of projects by priorities and regulate the use of investment resources.